Why Should Businesses Support Public Health?. Issue 7 (September 2021) - Myburgh, Inge; Goetzel, Ron Z.; Roemer, Enid Chung; Kent, Karen B.
The COVID-19 pandemic presents a unique opportunity to gain support from the business community for rebuilding a more effective and resilient public health infrastructure in the U.S. This commentary provides the rationale for more engaged business involvement in efforts to promote public health during the time of COVID-19. Drawing on the current pandemic, the commentary highlights the implications of a fragmented public health system for businesses and the nation at large, the shortcomings of which are apparent as never before.